IMPLEMENTASI PERDA KOTA SEMARANG NOMOR 2 TAHUN 2012 PADA KASUS RETRIBUSI PELAYANAN PARKIR DI TEPI JALAN UMUM JALAN PANDANARAN - Sulsiah, Nur Farida; Subowo, Ari; Maesaroh, Maesaroh (Jurusan Administrasi Publik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Diponegoro, 2015)
Retribution parkirng service at the edge of the public road is one of the pocket of local reveue receipts of Semarang. Policies parking of retribution collection services by public road set in Semarang City Regulation No.2 of 2012. Retribution parking services at the edge of the public road itself is the collection of retribution for service by the public treet parkirng is provide by the city of Semarang. Although the existing regulations governing the of retribution collection parking services at the edge of the public road Semarang, the target of retribution is not maximized. In addition, there are still illegal parking and illegal parking attendants. This study aims to determine how to implementation of the policy of retribution collection services by the public street parking Semarang also to know the driving factors and obstacles in the implementation of the polivy. The method use in this research is descriptive qualitative method. In this study the author used four appropriateness of the policy of Riant Nugroho to determine the effectiveness of policy implementation and implementation of Edwards III theory to determine the factors that effect the implementation of the policy. The results showed that the fact service retribution policy on public road flexible edge in the field so as to make the policy is weak and has not been able to overcome the problem of parking in the city of Semarang. The ammount of red tape involved and the limited resources especially supporting facilities for parking attendants become an obstacle to the implementation of policies in the edge of the parking service retribution public roads.